Nonrelationship sex and the college student population - White, Mallary L. (Kansas State University, 2013)
Nonrelationship sex is quite common on college campuses despite the number of risks involved. This report provides a review of the nonrelationship sex research literature and focuses on definitions, prevalence, predictive factors and influences, potential negative outcomes, and gender differences surrounding nonrelationship sex. The Nonrelationship Sex Emphasis Checklist (NSEC) was created for college sex educators in response to this review. This report provides an evaluation of the Sexual Health Awareness Peer Educators program at Kansas State University using the NSEC and a general curriculum assessment. Based on this evaluation, recommendations are given for SHAPE. Recommendations for future programming and research also are given.
Keywords: Risky sexual behaviorNonrelationship sex; Hook up; Friends with benefits; College students; Individual & Family Studies (0628)